Post Operational Optimization of Adaptive Overload Shedding Protection in the Bali Island Sub-system using the ADS Simulation - Sofwan, A.; Multi, A.; P.W, D. Madya; Abrianto, H. Heru (International Journal of Advanced Multidisciplinary, 2024)
The Bali electrical network sub system is supported by the Java-Bali power transfer assisted by the Bali power generation. Most of these power plants are not economical, so the Java-Bali power transfer is prioritized. If an island operation occurs, the Bali sub system loses most of the power that supports its load. This loss of power can result in a black out. The Bali sub system must perform overload shedding equal to the loss of Java-Bali power transfer. However, because the magnitude of the Java-Bali power transfer is very dynamic, the amount of Over Load Shedding (OLS) is difficult to predict, so an optimization system is required that can calculate the amount of OLS according to the Java-Bali power transfer at any time. The optimization system can also determine OLS targets before Faults occur based on the Priority Scale. To ensure that the Optimization System has worked properly, an Adaptive Defense Scheme (ADS) simulation was created. In this simulation, the optimization system will be tested using the ADS simulation series. In this simulation, the optimization system will be tested using the ADS simulation series. This system is simulated so that it can work OLS target off contact. This system will be tested for the suitability of the load selection with the amount of Java-Bali power transfer. The load selection is compared with manual calculations using the same method to ensure the optimization system calculations are appropriate. Comparison between the selection of targets for the optimization system with calculations, and working contacts is made by making a suitability matrix. From the tests carried out, it was obtained that OLS System Optimization System target size was calculated with a maximum deviation of 5.5%, a minimum deviation of 0.037%, and an average deviation of 1.03%. The system is also capable of selecting targets with 100% accuracy and can also perform MTDS digital output according to 100% accuracy, that the operational system efficiency can be achieved very significantly.